2021
DOI: 10.1038/s41377-021-00560-3
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of epitaxial growth of strain-relaxed GaN films on graphene/SiC substrates for long wavelength light-emitting diodes

Abstract: Strain modulation is crucial for heteroepitaxy such as GaN on foreign substrates. Here, the epitaxy of strain-relaxed GaN films on graphene/SiC substrates by metal-organic chemical vapor deposition is demonstrated. Graphene was directly prepared on SiC substrates by thermal decomposition. Its pre-treatment with nitrogen-plasma can introduce C–N dangling bonds, which provides nucleation sites for subsequent epitaxial growth. The scanning transmission electron microscopy measurements confirm that part of graphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…In addition, the substrate used in the vdW III-nitride epitaxy also plays an important role because it affects the crystal orientation and the strain of the vdW epilayers. The growth of 2D h-BN and 3D III-nitride semiconductors has been performed on different types of substrates ranging from metals (Ni, Cu) to dielectric surfaces and graphene. , However, sapphire substrates are standard in industry and exhibit high hardness, good light transmittance, and thermal stability. , As an anisotropic material, different crystal orientations have different surface and mechanical properties and, thereby, can have an impact on vdW epitaxy. It has been reported that GaN grown directly on a - and m- plane sapphire substrates is nonpolar and semipolar, which leads to better luminescence efficiency of the devices compared with GaN grown on c -plane sapphire, which suffers from the quantum-confined stark effect due to strong piezoelectric fields .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the substrate used in the vdW III-nitride epitaxy also plays an important role because it affects the crystal orientation and the strain of the vdW epilayers. The growth of 2D h-BN and 3D III-nitride semiconductors has been performed on different types of substrates ranging from metals (Ni, Cu) to dielectric surfaces and graphene. , However, sapphire substrates are standard in industry and exhibit high hardness, good light transmittance, and thermal stability. , As an anisotropic material, different crystal orientations have different surface and mechanical properties and, thereby, can have an impact on vdW epitaxy. It has been reported that GaN grown directly on a - and m- plane sapphire substrates is nonpolar and semipolar, which leads to better luminescence efficiency of the devices compared with GaN grown on c -plane sapphire, which suffers from the quantum-confined stark effect due to strong piezoelectric fields .…”
Section: Introductionmentioning
confidence: 99%
“…Over recent years, an emerging method named quasi-van der Waals (QvdW) epitaxy or remote epitaxy based on two-dimensional (2D) material has been proposed for high-quality heteroepitaxial growth of group-III nitrides 27 30 . The widely studied 2D material, graphene (Gr) has been incorporated as a buffer layer for the epitaxial growth of nitrides to effectively alleviate the lattice and TEC mismatches between the epilayer and the substrate 31 33 . Besides, it is worth mentioning that the metal adatoms of nitrides have a tiny migration barrier on the Gr surface, which can undoubtedly promote the 2D growth trend of nitride films 34 , 35 .…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, graphene, known as the first invented 2D material, has attracted extensive attention for many applications [44]. Its unique mechanical characteristics, electronic structures and optical properties make it applicable in fields such as solar cells, LED transistors, sensors and catalysts [45][46][47][48]. More importantly, the properties of 2D materials can be easily tuned via doping atoms, hybridizing with other nanostructures, surface engineering and defect generation, further improving their electronic properties and catalytic performance.…”
Section: Introductionmentioning
confidence: 99%